A bibliometric analysis of fungal volatile organic compounds - Kustrim Cerimi; Dierk-Christoph Pöther; Stefanie Klar (Fungal Biology and Biotechnology)
Abstract Background Fungal volatile organic compounds (fVOCs) serve as crucial mediators in ecological interactions and hold significant potential for applications in agriculture and biotechnology. Fungi establish inter-organism communication through volatile molecules, enabling them to regulate plant growth and interact with diverse soil-dwelling organisms. This study integrates a comprehensive literature survey and bibliometric analysis to capture the complexity and interdisciplinary nature of fVOC research, drawing on PubMed, Google Scholar, and Scopus databases spanning 2000 to 2023. Results The findings highlight the role of fVOCs as essential chemical messengers in inter-organismic communication, their contribution to sustainable agricultural practices as plant growth promoters, and their significance in human sensory perception, particularly in culinary contexts. Our bibliometric analysis of 3,738 publications maps fVOC research trends worldwide using co-occurrence and -citation analyses. The latter uncovered an early research focus on yeast fermentation and antimicrobial activity, which has since expanded to sustainable agriculture, biofumigation, endophytic fungi, and the development of advanced analytical techniques. Emerging research clusters focus on plant–fungus communication, the biotechnological production of aroma compounds, and the influence of fVOCs on human sensory experiences. Conclusions The fVOC research field has matured during the last two decades. Promising avenues for future exploration include the improvement of crop resilience, the advancements of eco-friendly technologies, such as biological pest management or VOC-driven fertilisation, and a better understanding of the intricate volatile communication that drives fungal interactions with other kingdoms of life.